KONSEP PENDIDIKAN ANAK SHALEH DALAM AL-QUR’AN SURAT LUQMAN AYAT 1-5 MENURUT TAFSIR AL-MUNIR KARYA WAHBAH AZ-ZUHAILI - Nurjanah, Teti; Azis, Abdul; Milah, Saepul (Program Studi Pendidikan Islam Anak Usia Dini, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, Ciamis Jawa Barat, 2025)
Zuhaili Wahbah in al-tafsir al-Munir explained that impetus for the pious education of children, among others, contained in a letter Luqman al-Quran verses 1-5. It describes among other things that education must be based on valid educational theory, and educators and learners should know the futuristic benefit from the educational process is done. Problems studied are: 1) How interpretasion of Koran of the letter Luqman verses 1-5 according to al-tafsir al-Munir ?; 2) How does the concept of pious children education according to the Koran letter Luqman verse 1 - 5 according to al-tafsir al- Munir ? By using descriptive methods, this research produced the conclusion that the concept of pious children's education according to the letter of the Koran verses 1-5 by Luqman in al-tafsir al-Munir include: a) the planning of education, principles of guidance and compassion, competence pious child, and knowledge about the benefits of futuristic education